APPLICATION OF MAKE A MATCH LEARNING MODEL TO IMPROVE MATHEMATICS LEARNING OUTCOMES IN CLASS VA OF STATE ELEMENTARY SCHOOL 1 PALEMBANG - Oktaria, Pelinsia; Hiltrimartin, Cecil; Manulang, Lilis Sri Jayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2025)
This study aims to improve students' mathematics learning outcomes through the application of the Make a Match learning model in class VA of SD Negeri 1 Palembang. The Make a Match model is a cooperative learning model that involves game elements in finding the right pair of cards, thus encouraging students to be more active, work together, and be directly involved in the learning process. The research method used is classroom action research (CAR) which is carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection. The subjects of this study were 28 students in class VA. Data were obtained through learning outcome tests and observations of student activities during the learning process. The results of the study showed an increase in student learning outcomes in each cycle after the implementation of the Make a Match model. This increase occurred because students were more motivated, enthusiastic, and active in participating in learning. Thus, the application of the Make a Match learning model can be an effective alternative to improve students' mathematics learning outcomes in elementary schools.